Akulturasi Budaya Madura dalam Konteks Keagamaan Berbasis Sistem Islamic Education - Yanto, Masti; Raimuna, Raisa; Abidin, Zeinal (Darajat: Jurnal Pendidikan Agama Islam, 2024)
This research discusses the phenomenon of Madurese cultural acculturation in a religiouscontext based on the Islamic education system. Madura, as a region with unique culturalrichness, faces challenges in integrating its local values with Islamic teachings. This researchaims to explore how the Madurese cultural acculturation process occurs within theframework of Islamic education, as well as its impact on the religious and social identity ofthe Madurese community. The research method used is qualitative with a case study approach. Data was collected through participant observation, in-depth interviews, anddocument analysis. The research results show that the acculturation process of Madureseculture in a religious context tends to produce a unique synergy between local traditions andIslamic values. This is reflected in the development of curricula, teaching methods andreligious practices that accommodate Madurese cultural values without sacrificing Islamicprinciples. The impact of this acculturation can be felt in a deeper understanding of localIslam which is closely related to Madurese local wisdom. However, challenges such as valueconflicts and resistance to change remain important factors that need to be overcome inimplementing this acculturation. In conclusion, Madurese cultural acculturation in thecontext of Islamic education is a dynamic process that requires an inclusive and sensitiveapproach to the cultural and religious identity of the Madurese people to achieve aharmonious balance between local traditions and Islamic teachings